Construction of the Discus Throw Test for Physical Education Students - Henjilito, Raffly; Yani, Ahmad; Zulkifli, Zulkifli; Setiawan, Budi Arif (Indonesian Journal of Sport Management, 2025)
The aim of this research is to make improvements in the discus throwing test. Components that are improved in the throwing process start from the discus handle, the rotating stage, the throwing stage until returning to the original movement stage. Usually the discus throwing test uses the furthest distance taken by the meter. To find out the discus throwing quality of physical education students at Riau Islamic University, of course there must be test instruments and test norms for these students. Based on the background above, it is important for this research to be carried out in order to create a standard discus throwing test instrument that complies with the latest IAAF regulations. The method in this research uses research and development methods. This research uses development with the Borg and Gall model which includes ten activities, namely: (1) research and information collecting, (2) planning, (3) develop preliminary form of product, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, (10) dissemination and implementation. The targets achieved in this research were physical education athletic students at Riau Islamic University. The population in this study was 40 people and the sample using a total sampling technique was 40 people. The instrument of this research is the discus throwing test. The data analysis technique in this research is (a) validity test using content validity and construct validity. The construct validity test was carried out by analyzing data from the discus throwing test results. The data obtained from the test was tested for validity using the SPSS computer program. (b) reliability test to describe the consistency of measurement results. The results of the discus throwing test instrument developed were correlated with the total score and had a validity of 0.790 and 0.790 which was greater than the r table (0.361). Meanwhile, the reliability result is 0.701, which is greater than the r table (0.361). The results of the validity of large group trials using the SPSS application with results obtained were 0.749, including the medium category. Based on data analysis, discus throwing skills were the lowest with a score of 87.91 and discus throwing skills were the highest with a score of 164.06.